KOMUNIKASI LINTAS AGAMA DALAM PERSPEKTIF ISLAM - Mujib Ridlwan (Al Hikmah: Jurnal Studi Keislaman, 2011)
Abstract: Cross-religion communication actually started at the time of the Prophet Muhammad SAW with the Charter of Medina, Medina Charter is the decision of the Prophet Muhammad that contains the basic provisions governing all aspects of life (ideology, politics, economics, social, cultural, defense, and security ) Medina community consisting of Muslims, Christians and Jews to coexist in a society.Indonesia multicultural and multi religious country should be able to continue the example of the Prophet in building cross-religion communication.Islam strongly encourages his people to establish communication with other religions, Islam has set an example in the forefront of interfaith communication through a constitution 'Charter of Medina' and the behavior of the Prophet Muhammad. There are violences in the name of religion the trigger because of economic inequality, religion only as a shield to commit violence, religious groups are so many emerging facilitate interreligious conflict ignited.